2022
DOI: 10.1111/tbed.14478
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiota of bats confers tolerance to influenza virus (H1N1) infection in mice

Abstract: Pathogens from wild animals cause approximately 60% of emerging infectious diseases (EIDs). Studies on the immune systems of natural hosts are helpful for preventing the spread of EIDs. Bats are natural hosts for many emerging infectious pathogens and have a unique immune system that often coexists with pathogens without infection.Previous studies have shown that some genes and proteins may help bats fight virus infection, but little is known about the function of the bat gut microbiome on immunity. Here, we t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 145 publications
(144 reference statements)
0
4
0
Order By: Relevance
“…dysbiosis) can negatively affect an individual's immune status [ 62 ]. Experimental studies have shown that GIT microbiota transplanted from great roundleaf bats ( Hipposideros armiger ) into antibiotic-treated mice altered immune cell levels and conferred greater resistance and survival to H1N1 influenza infection compared with control groups, indicating the GIT microbiome can interact with and change the host immune system [ 63 ]. Additionally, lipopolysaccharide injections in R. aegyptiacus induced significant and rapid (24–48 h) changes to the composition and diversity of gut microbial communities [ 64 ].…”
Section: Research At the Individual Scale: Metrics For Assessing Bat ...mentioning
confidence: 99%
“…dysbiosis) can negatively affect an individual's immune status [ 62 ]. Experimental studies have shown that GIT microbiota transplanted from great roundleaf bats ( Hipposideros armiger ) into antibiotic-treated mice altered immune cell levels and conferred greater resistance and survival to H1N1 influenza infection compared with control groups, indicating the GIT microbiome can interact with and change the host immune system [ 63 ]. Additionally, lipopolysaccharide injections in R. aegyptiacus induced significant and rapid (24–48 h) changes to the composition and diversity of gut microbial communities [ 64 ].…”
Section: Research At the Individual Scale: Metrics For Assessing Bat ...mentioning
confidence: 99%
“…The commensal microbiota persistently stimulates the expression of TLR7, MyD88, IRAK4, TRAF6, and NF-kB in TLR7 signaling pathway, defending the host against influenza virus [ 20 ]. Moreover, fecal microbiota transplantation (FMT) has been proposed as a therapeutic intervention for influenza viral infection [ 146 , 147 , 148 ]. FMT involves the transfer of fecal microbiota from donors to recipients in order to restore or modify gut microbial diversity and function.…”
Section: The Role Of Commensal Microbiota In Influenza Virus Infectionmentioning
confidence: 99%
“…Previous studies demonstrate that the innate immune system of unstimulated bat tissues remain switched on due to constitutive expression of three IFN-α gene that limit viral replication without the presence of high antibodies titre ( 53 , 65 , 268 ). Moreover it has been demonstrated that bat microbiome from Great Himalayan Leaf-nosed bats ( Hipposideros armiger ) transplanted into H1N1 infected mice, reduces the inflammatory response and increases survival rate being that associated with increased production of flavonoid and isoflavones as well as with the quick innate immune response induced by the bat fecal transplanted microbiota, thus conferring mouse tolerance to influenza virus (H1N1) infection ( 269 ).…”
Section: Avoidance Resistance and Tolerance To Virusesmentioning
confidence: 99%